Penjadwalan Produksi Campur Merata Untuk Memenuhi Permintaan Konsumen Melalui Sistem Produksi Just In Time - Maryati, Wahyu Enie (Jurnal Teknik Industri, 2001)
Thep rogres of challanging and there are more kind of customers need, make a company can't sell single fixed product in function, model, and measurement. The reacted ability to respon market is the most important thing of PT. Wavin Duta Jaya as one of company which produce PVC pipe that have many kinds and size to reach maximum profit.